Infant and Young Child Feeding by Mothers in a Selected Rural Area of Mymensingh (Community Based Medical Journal, 2016)
This study was done to know about infant and young child feeding by mothers in a selected rural area of Mymensingh and to assess nutritional status of infant and young child. This was a descriptive cross-sectional study. The sample size was 625. Sample size and study area was purposively selected. The study was conducted from December 2016 to January 2017 in Churkhai and Winnerpar villages of Bhavokhali union of Sadar upazila Mymensingh. Data were collected on a predesigned questionnaire by direct interviewing the respondents. Data analysis was done by SPSS version 16. A total of 625 mothers who had one child aged between newborn to 24 months participated in the study. Age of mothers ranged from 15 years to 50 years. Mean age of mothers was 24.56 years and standard deviation 5.36 years. Most of the mothers belonged to 15 to 24 years of age. The age of children ranged from newborn to 24 months. Mean age of children was 15.16 months, standard deviation 7.51 months. Majority of children belonged to 19 to 24 months. Majority (54.72%) had normal nutrition. Breast feeding continued up to the age when interviewed, offering colostrums and breast feeding given within half an hour after delivery were excellent among 63.36% of mothers. Weaning in due time, appropriate servings and weaning food appropriate were excellent among 74.80% of mothers of weaning age child. Exclusive breast feeding 74.02% and breast feeding continued up to the age of 24 months were 79.33% were good. Infant and Young Child Feeding practices observed in this study though better than other studies, needs more attention for improved child nutrition and survival.CBMJ 2016 July: Vol. 05 No. 02 P: 21-25